La educación en Colombia: 1918-1957 (2022)
It is easy to abstractly postulate the relations between education and society; the hard part is to show specifically the reciprocity of this bound. Which is the most suggestive strategy to exhibit their push and eficacy in historical perspective? By the study of the consequences of the educative politics. The plans are ideas, forecasts consigned in the Goverments dispositions or int he multiple and variable Parliament legislations. Programs only are real when they reach to the population or determined sectors of it, this is, when they try to transform it in one or other direction. This is what Aline Helg does in this book, through the inteligent use of a rich information derived from public and private fonts: State documents, ecclesiastical papers, oficial statistics, press data, school institucions archives and interviews with teachers and education dirigents.